Error-voltage-based open-switch fault diagnosis strategy for matrix converters with model predictive control method - Dan, Hanbing; Peng, Tao; Su, Mei; Deng, Hui; Zhu, Qi; Zhao, Ziyi; Wheeler, Patrick (IEEE, 2017)
This paper proposes an error-voltage based open-switch fault diagnosis strategy for matrix converter (MC). A finite control set model predictive control (FCS-MPC) method is used to operate the MC. The MC system performances under normal operation and under a single open-switch fault operation are analyzed. A fault diagnosis strategy has also been implemented in two steps. First, the faulty phase is detected and identified based on a comparison of the reference and estimated output line-to-line voltages. Then, the faulty switch is located by considering the switching states of the faulty phase. The proposed fault diagnosis method is able to locate the faulty switch accurately and quickly without additional voltage sensors. Simulation and experimental results are presented to demonstrate the feasibility and effectiveness of the proposed strategy